Medical biochemistry - Baynes, John W.; Dominiczak, Marek H. (Saunders Elsevier, 2014)
The new edition of Medical Biochemistry gives access to all of the latest information on basic and clinically focused genetic and molecular biology. Featuring a team of contributors that includes investigators involved in cutting-edge research as well as experienced clinicians, this updated medical textbook offers a unique combination of both research and practice that's ideal for today's problem-based integrated courses